Opinion 2436: The work “The White-cheeked Geese: Branta canadensis, B. maxima, B. ‘lawrensis’, B. hutchinsii, B. leucopareia, and B. minima. Taxonomy, ecophysiographic relationships, biogeography, and evolutionary considerations, Volume 1, Eastern taxa; Volume 2, Western taxa, biogeography, and evolutionary considerations” by Harold C. Hanson: suppressed for nomenclatural purposes - ICZN (Bulletin of Zoological Nomenclature, 2019)
The International Commission on Zoological Nomenclature has suppressed for nomenclatural purposes the two-volume work “The White-cheeked geese: Branta canadensis, B. maxima, B. ‘lawrensis’, B. hutchinsii, B. leucopareia, and B. minima. Taxonomy, ecophysiographic relationships, biogeography, and evolutionary considerations” by Harold C. Hanson.